Maternal health service utilization from urban health extension professionals and associated factors among women who gave birth in the last one year in Ambo town, Oromia regional state, Ethiopia, 2018 - Kebede Megerssa Berri; Yeshi Kumera Adaba; Teka Girma Tarefasa; Nagasa Dida Bededa; Daniel Belema Fekene (BMC, 2020)
Abstract Background Despite the existence of urban and rural health extension workers maternal mortality and morbidity remain, as a public health problem in Ethiopia. The utilization of maternal health services from UHE-ps is key activities, which contribute to the reduction of maternal morbidity and mortality. This study aimed to assess maternal health service utilization from urban health extension professionals and associated factors among women who gave birth in the last one year in Ambo town. Methods Community-based cross-sectional study conducted from February to March 2018 among women who gave birth in the last year before the study period, in Ambo town, Oromia, Ethiopia. The Data collections were through face-to-face interview, the Focus discussion group was done using a semi-structured questionnaire. Descriptive, bivariate and multiple logistic regressions computed by SPSS version 20. Statistical significance was considered at p < 0.05 and the strength of statistical association was assessed by odds ratio with 95% confidence intervals. Result From the total respondents, only 57(14.2%) women utilized maternal health services from urban health extension professionals during their recent birth. Regarding maternal health services utilization from urban health extension professional's ANC, Delivery and PNC were 159 (39.7%), 115 (28.7%) and 76 (19%) respectively. The variables, such as graduated as model family (AOR: 2.4; 95% C I: 1.20, 4.78), home visit during pregnancy within month (AOR: 11.6; 95% CI: 3.60, 37.17), awareness on pregnancy danger sign (AOR: 3.8; 95% CI: 1.62, 8.92) and parity (AOR: 2.8; 95% CI: 1.06, 7.61) were factors affecting maternal health services utilization from urban health extension professionals. Conclusion The utilization of maternal health services from urban health extension professionals was found to be low. Being graduated as a model family, awareness on pregnancy danger sign, parity and urban health extension professional's home visit during pregnancy had a positive statistically significant association with maternal health services utilization from urban health extension professionals. Therefore, considering the identified associated variables could increase and sustain maternal health services utilization from urban health extension professionals.